Development of A Basic Chemistry E-Book Enhanced with Multiple Representations and STEM Activities - Yunita Susanti, Laily; Hasanah, Rafiatul (Journal of Tropical Chemistry Research and Education, 2025)
Chemistry concepts are generally abstract so they require teaching materials that visualize those abstract concepts. The aims of this study were to develop a Basic Chemistry E-Book enhance with multiple representations and STEM approach. This study used a research and development model modified from the ADDIE model which consists of 5 stages, namely: (1) Analysis (analysis of students’ characteristics and course objectives), (2) Design (design of e-book and research instruments), (3) Develop (e-book production), (4) Implementation (expert judgement and field trials), and (5) Evaluation (the effectiveness test and revision of e-book). Research result showed that the feasibility of e-book based on the expert judgement got 93.75% as a score on the material feasibility component, 100% as a score of feasibility component and 95.40% as a score of the language and STEM component. Furthermore, the results of small-scale field trials obtained a percentage of 86% and large-scale field trials obtained a percentage of 87%. The effectiveness test of e-book got score 0,643 means e-book was effective enough for using in learning chemistry. Based on this study, e-book for Basic Chemistry Course based on multiple representations with the STEM approach is appropriate for being used in general chemistry course.